2008
DOI: 10.5551/jat.e581
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pitavastatin on Lipid Profiles and High-Sensitivity CRP in Japanese Subjects with Hypercholesterolemia: Kansai Investigation of Statin for Hyperlipidemic Intervention in Metabolism and Endocrinology (KISHIMEN) Investigatars

Abstract: Aim:The effect of pitavastatin on high-sensitivity C-reactive protein (hs-CRP) has not been reported, yet, in humans. We, therefore, investigated the effects of pitavastatin on lipid profiles and hs-CRP in Japanese subjects with hypercholesterolemia. Methods: The subjects were 178 Japanese with hypercholesterolemia, including 103 (58%) with type 2 diabetes. Pitavastatin (1 − 2 mg/day) was administered for 12 months. Serum low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 27 publications
4
40
0
Order By: Relevance
“…An in vitro study demonstrated that pitavastatin inhibited RLP-induced macrophage foam cell formation, at least in part through regulation of the apoB48 receptor expression, a novel receptor for RLPs 16) . A recent study by Koshiyama et al showed that the administration of pitavastatin significantly reduced serum remnant-like particle cholesterol (RLP-C) levels by 22.8%, together with serum LDL and hs-CRP levels 17) , which suggested that pitavastatin improved lipid profiles and prevented atherogenic changes.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study demonstrated that pitavastatin inhibited RLP-induced macrophage foam cell formation, at least in part through regulation of the apoB48 receptor expression, a novel receptor for RLPs 16) . A recent study by Koshiyama et al showed that the administration of pitavastatin significantly reduced serum remnant-like particle cholesterol (RLP-C) levels by 22.8%, together with serum LDL and hs-CRP levels 17) , which suggested that pitavastatin improved lipid profiles and prevented atherogenic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in our study, 39% of patients were taking statins. Because hsCRP levels were reported to be affected by the use of statins [31][32][33] , the inclusion of patients who were taking statins may have confounded the results of the correlations between hsCRP levels and coronary or aortic atherosclerosis; however, now that statin use in patients with CAD is very common, the exclusion of patients taking statins would render our results inapplicable to general patients with CAD.…”
Section: )mentioning
confidence: 94%
“…In two cases, pitavastatin was suggested to improve not only LDL-C and HDL-C, but also HOMA-IR and GIR. Pitavastatin has pleiotropic effects which do not depend on lipid diminishing actions such as the anti-inflammatory effect [9], antioxidant effect [10] and endothelial function improvement [11]. In addition, it has been confirmed that pitavastatin increases adiponectin in hypercholesterolemic and patients with type 2 diabetes [12], and these actions may contribute to the amelioration of insulin resistance.…”
Section: Discussionmentioning
confidence: 97%